2012
DOI: 10.2140/agt.2012.12.1487
|View full text |Cite
|
Sign up to set email alerts
|

CyclicAstructures and Deligne’s conjecture

Abstract: First we describe a class of homotopy Frobenius algebras via cyclic operads which we call cyclic A 1 algebras. We then define a suitable new combinatorial operad which acts on the Hochschild cochains of such an algebra in a manner which encodes the homotopy BV structure. Moreover we show that this operad is equivalent to the cellular chains of a certain topological (quasi)operad of CW-complexes whose constituent spaces form a homotopy associative version of the cacti operad of Voronov. These cellular chains th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…For the definition of the filtration F a O M and verification of (i), see Remark 7.6. To verify (ii), it is sufficient to check that the generators of the operad T S ∞ (see [27] Section 4.1) preserve the length filtration, and this is straightforward from (i). The isomorphism H * (L a M ) ∼ = H * (F a O M ) in (iii) will be defined in Section 8.2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the definition of the filtration F a O M and verification of (i), see Remark 7.6. To verify (ii), it is sufficient to check that the generators of the operad T S ∞ (see [27] Section 4.1) preserve the length filtration, and this is straightforward from (i). The isomorphism H * (L a M ) ∼ = H * (F a O M ) in (iii) will be defined in Section 8.2.…”
Section: Resultsmentioning
confidence: 99%
“…The operad f P in our statement is the operad T S ∞ , which is introduced in [27] Section 4. The inclusion of operads P → f P follows from Lemma 5.9 in [27]. The sign for the operator ∆ in the statement (i) will be discussed in Section 2.5.4.…”
Section: Now Let Us State a Version Ofmentioning
confidence: 99%
“…The added difficulty, is that for cacti one is dealing with a bi-crossed product and not just a semi-direct product. The cyclic A ∞ version again based on cacti is contained in [47]. 5.1.…”
Section: Discussion: Relations To Other E 2 Operads Application and mentioning
confidence: 99%
“…In [33] we showed that one can relax the condition of A being associative to A 1 for the brace operations, aka. A 1 -Deligne conjecture, and in [51] the same was done tor the BV operators, aka. cyclic A 1 conjecture.…”
Section: 23mentioning
confidence: 99%